Did judge dismiss coach's due process claim?. Issue 9 (18th December 2020) - Lyerly, Eric
Abstract : T he plaintiff was the head coach of the Mohawk Valley Community College women's basketball team. At some point during the 2017–18 basketball season, the MVCC human resources director received an anonymous tip claiming the plaintiff had improperly loaned money to a student‐athlete in violation of National Junior College Athletic Association rules.